Positive serological tests for syphilis and administration of intravenous immunoglobulin. Issue 1 (5th February 2007) - Constable, S A; Parry, C M; Enevoldson, T P; Bradley, M
Abstract : We report the case of a man who tested positive for syphilis following the intravenous administration of human normal immunoglobulin as part of the treatment of Guillain-Barré syndrome. The chronology of the testing suggested the passive acquisition of treponemal antibody. This phenomenon is not widely documented in the medical literature, but is a theoretical risk of treatment, and serves as a reminder to be cautious in the interpretation of such serological tests.